PENGARUH DIGITAL MARKETING DAN ENDORSER NON-CELEBRITY TERHADAP MINAT BELI MELALUI BRAND IMAGE SEBAGAI VARIABLE INTERVENING (STUDI KASUS DI GRANDKEMANG JAKARTA) - Aldilla, Athiyah; Nurbaeti; Mumin, Adhi Trirachmadi (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2024)
The advancement of digital technology has transformed how the hospitality industry markets its products through digital marketing and non-celebrity endorsement. This study analyzes the influence of digital marketing and non-celebrity endorsers on purchase intention with brand image as a mediating variable at Hotel Grandkemang Jakarta. Academically, the study fills a literature gap regarding the effectiveness of non-celebrity endorsements in the hospitality industry while offering practical insights for hotel managers in the digital era. The study employs a descriptive quantitative approach using SEM-PLS analysis based on data from 100 respondents. The results show that non-celebrity endorsers significantly influence brand image (coefficient 0.593) and purchase intention (coefficient 0.397), both directly and through brand image mediation (mediation coefficient 0.276). Conversely, digital marketing only affects brand image (coefficient 0.398) but has no significant impact on purchase intention (coefficient 0.125). The findings support the Meaning Transfer Model, emphasizing the role of brand image in linking marketing strategies with purchase decisions. Practically, the study recommends using credible non-celebrity endorsers to enhance brand image and purchase intention. Future research should explore additional variables such as online reviews and discounts while expanding the study's geographic coverage.